Detection of exogenous floating marine debris - Paige, Maria (2015)
Paige, M., & Painho, M. (2015). Detection of exogenous floating marine debris: An overview of techniques associated with remote sensing. In Water Resources Management VIII (Vol. 196, pp. 537 - 548). (WIT Transactions on Ecology and the Environment). DOI: 10.2495/WRM150461